The Draining Lymph Node in Rheumatoid Arthritis: Current Concepts and Research Perspectives. (22nd February 2015) - Benaglio, Francesca; Vitolo, Barbara; Scarabelli, Martina; Binda, Elisa; Bugatti, Serena; Caporali, Roberto; Montecucco, Carlomaurizio; Manzo, Antonio
Abstract : Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease of unknown aetiology, leading to progressive damage of bone and cartilage with functional impairment and disability. Whilst the synovial membrane represents the epicentre of the immune-inflammatory process, there is growing evidence indicating the potential involvement of additional anatomical compartments, such as the lung, bone marrow, and secondary lymphoid tissues. Draining lymph nodes represent the elective site for tissue immune-surveillance, for the generation of adaptive immune responses and a candidate compartment for the maintenance of peripheral tolerance. Despite the precise role of the juxta- and extra-articular lymph node stations in the pathogenesis of RA remaining poorly defined, several lines of research exploiting new technological approaches are now focusing on their assessment as a potential new source of pathobiologic information, biomarkers, and complementary therapeutic targets. In this review we present an updated overview of the main concepts driving lymph node research in RA, highlighting the most relevant findings, current hypothesis, and translational perspectives.